Presenting indigenous language of Suwawa in terms of clause structure - Nawari, Ahmad; Didipu, Herman; Muslimin, Muslimin; Hadriana, Hadriana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
This research is aimed to describe Suwawa language clauses (SLC) in local content subject at elementary schools. It focuses on introducing SLC and the description of types of SLC. The method used is the descriptive method. SLC Data were obtained from utterances and speech by native of Suwawa. Observation, interviews, and note-taking were used to collect the data. A distribution method on the functions of SCL was used to analyze the data. The research findings revealed that introducing Suwawa is very important since the language functions as a self-identity and a filter from global culture penetration. The language has 13 types of clauses grouped into 5 based on (1) the core elements, (2) internal structure, (3) position in the sentence, (4) the presence or absence of negation elements in the predicate, and (5) the functional category. Research shows that introducing the Suwawa language is important not only to preserve it but also to give Gorontalo, Sulawesi Indonesia's youth a sense of self and cultural identity against globalization.